2003
DOI: 10.1016/s0304-3959(02)00323-8
|View full text |Cite
|
Sign up to set email alerts
|

Striatal dopamine D1 and D2 receptors in burning mouth syndrome

Abstract: Animal studies have indicated that the nigrostriatal dopaminergic system is involved in central pain modulation. In a recent positron emission tomography (PET) study, we demonstrated presynaptic dysfunction of the nigrostriatal dopaminergic pathway in burning mouth syndrome, which is a chronic pain state. The objective of the present study was to examine striatal dopamine D1 and D2 receptors in these patients. We used 11C-NNC 756 and 11C-raclopride to study D1 and D2 receptor binding in a PET study in ten burn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
147
1
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(168 citation statements)
references
References 44 publications
7
147
1
9
Order By: Relevance
“…Basal ganglia structures are not commonly reported in the acute pain literature (Jones et al, 1991;Casey et al, 1994) but involvement in the processing of nociceptive information (Tracey et al, 2000), including attention to noxious information, motor preparation and response selection are increasingly recognized, and dedicated nociceptive pathways to the striatum have been identified (Braz et al, 2005). Iardola and colleagues have observed bilateral activation of the putamen with capsaicininduced pain and the basal ganglia have also been found to play a role in chronic pain conditions such as atypical facial pain (Hagelberg et al, 2003a) and burning mouth syndrome (Hagelberg et al, 2003b). The reader is referred to an excellent review for further consideration of the role of the basal ganglia in pain perception (Chudler and Dong, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Basal ganglia structures are not commonly reported in the acute pain literature (Jones et al, 1991;Casey et al, 1994) but involvement in the processing of nociceptive information (Tracey et al, 2000), including attention to noxious information, motor preparation and response selection are increasingly recognized, and dedicated nociceptive pathways to the striatum have been identified (Braz et al, 2005). Iardola and colleagues have observed bilateral activation of the putamen with capsaicininduced pain and the basal ganglia have also been found to play a role in chronic pain conditions such as atypical facial pain (Hagelberg et al, 2003a) and burning mouth syndrome (Hagelberg et al, 2003b). The reader is referred to an excellent review for further consideration of the role of the basal ganglia in pain perception (Chudler and Dong, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a predominance of pain in the off period and may be related to increase of stiffness 3,4,23 . The onset of pain on the most affected body side does not mean that pain is caused only by stiffness and/or bradykinesia, a hypothesis that could show that both the pain and motor symptoms share similar mechanisms, what means that modulation of pain could be performed by dopaminergic pathways on basal ganglia, where the lack of dopamine leads to a painful condition 10,24,25 .…”
Section: Methodsmentioning
confidence: 99%
“…This, plus other data, strongly suggests that there is a dysfunction of the small diameter afferent sensory fibres in burning mouth syndrome. Imaging studies in patients have also suggested central nervous system changes (Jääskeläinen et al, 2001;Hagelberg et al, 2003).…”
Section: Pathogenesismentioning
confidence: 99%